Unraveling the link between inflammatory bowel disease and perianal abscess: insights from bidirectional and multivariable Mendelian randomization study - Haoqi Zhu; Jingyi Pan (BMC Gastroenterology)
Abstract Background Emerging epidemiological studies have identified associations between perianal abscess (PA) and inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), though the pathophysiological mechanisms underlying their comorbidity remain incompletely understood. To elucidate potential causal relationships between these clinical entities, we conducted a comprehensive investigation employing bidirectional two-sample Mendelian randomization (MR) analysis complemented by multivariable Mendelian randomization (MVMR) methodology. This analytical approach enables systematic evaluation of causal directionality while accounting for potential confounding factors inherent in observational studies. Methods To establish valid instrumental variables, independent single nucleotide polymorphisms (SNPs) were selected from genome-wide association study (GWAS) summary statistics of European ancestry populations. Data for IBD were sourced from the IEU OpenGWAS repository, while PA datasets were obtained from FinnGen consortium and UK Biobank resources. Our bidirectional MR framework incorporated five complementary analytical methods: inverse variance weighted (IVW), weighted median, MR-Egger regression, weighted mode, and simple mode estimators. Methodological robustness was ensured through comprehensive sensitivity analyses: horizontal pleiotropy was evaluated via MR-Egger intercept testing, heterogeneity quantified using Cochran’s Q statistic, and outlier detection implemented through MR-PRESSO (Mendelian Randomization Pleiotropy Residual Sum and Outlier) with supplementary leave-one-out validation to assess individual SNP influence on causal estimates. Results Genetic liability analyses using IVW estimation revealed IBD) and its principal subtypes as risk factors for PA. In the discovery cohort, IBD conferred a 20% increased PA risk (OR = 1.20, 95%CI = 1.12–1.31, p = 5.68 × 10⁻⁵), with subtype-specific effects for CD (OR = 1.15, 95%CI = 1.06–1.24, p = 0.0004) and UC (OR = 1.11, 95%CI = 1.01–1.21, p = 0.027). These associations replicated consistently in the independent cohort (IBD: OR = 1.17, 95%CI = 1.09–1.27, p = 3.92 × 10⁻⁵; CD: OR = 1.12, 95%CI = 1.04–1.21, p = 0.002; UC: OR = 1.13, 95%CI = 1.03–1.24, p = 0.009). Conversely, IVW-based bidirectional analysis demonstrated non-significant associations between PA liability and IBD progression across both cohorts (all p > 0.05). Confounder-adjusted MVMR analyses confirmed direct causal effects of IBD (encompassing CD and UC) on PA risk after accounting for pleiotropy. In exploration cohorts, ulcerative ileocolitis in CD exhibited nominal association with elevated perianal disease risk (OR = 1.18, 95%CI = 1.01–1.38, p = 0.04) in hypothesis-generating analyses. Conclusions Our analyses demonstrated significant associations between PA and both principal IBD subtypes (UC and CD), underscoring the necessity for mechanistic investigations into shared pathophysiology within the IBD spectrum.